Malaysian Nature Education in Preschool (MYNEPS) intervention : pre and post assessment - Mohd Allif Abu-Yazid,; Farah Shafawati Mohd-Taib,; Nurhafizah Abdul-Musid,; Nurul Eizzaty Sohimi,; Suziyani Mohamed,; Haryanti Mohd Affandi,; Abdul Halim Masnan,; Faszly Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Malaysian Nature Education in Preschool (MyNEPs) is an initiative to incorporate nature education in the preschool syllabus. It involves learning and hands-on practice in a natural environment setting on five nature elements (climate, flora, fauna, insects, and microbes). This research aims to assess the efficacy of the MyNEPs module towards preschool children through pre-, intervention, and post-assessment. This research adopted an experimental research design using quantitative approaches. A total of 29 preschool children from Bangi, Selangor were involved in this study. Data collected were analyzed using descriptive and inferential statistics involving normality tests and paired sample t-test. The data normality was measured using the Shapiro-Wilk test, and the result indicated that the data is normally distributed where p=0.072 > 0.05. The overall t-test result shows significant differences (p=0.006) between pre- and post-achievement, with the total mean of post-test was higher with 35.90 than pre-test achievement with 33.59. This result indicated that this module significantly contributes to children's performance on nature prior to the intervention program. As a result, this study shows that the nature education program proposed has improved preschool children's knowledge of the natural environment. Nature education is essential to enhance creativity, problem-solving, and cognitive abilities, thus improving academic performance and setting a strong foundation for science and technology. Therefore, it is suggested that the MyNEPs module should be applied to all preschools premises in Malaysia.